1993
DOI: 10.1007/bf00237431
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of protoplast culture protocols for Beta vulgaris L. (sugar beet)

Abstract: The effects of NaCl, feeder cells and the embedding of protoplasts in calcium alginate have been investigated in an attempt to improve culture conditions of recalcitrant sugar beet (Beta vulgaris L.) mesophyll protoplasts. While the use of NaCl in all instances proved detrimental to protoplast development, the other two treatments had clear beneficial effects. Minimum plating densities, necessary to sustain cell division, could be reduced to <5% (<4000 protoplasts / ml) of the control levels and plating effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…interested genes into the protoplasts was limited by the difficulty of regenerating plantlets from protoplasts (Hall et al, 1993(Hall et al, , 1996Sevenier et al, 1998). When calluses were used as the material for transformation, transgenic cells could be easily obtained, but the regeneration of plantlets from the transgenic calluses was difficult (Paul et al, 1987;Krens et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…interested genes into the protoplasts was limited by the difficulty of regenerating plantlets from protoplasts (Hall et al, 1993(Hall et al, , 1996Sevenier et al, 1998). When calluses were used as the material for transformation, transgenic cells could be easily obtained, but the regeneration of plantlets from the transgenic calluses was difficult (Paul et al, 1987;Krens et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the beet cultivars were recalcitrant and the regeneration of plantlets from calluses was not as expected. Until now only a few genotypes were successfully transformed (Lindsey and Gallois, 1990;Paul et al, 1990;Fry et al, 1991;D'Halluin et al, 1992;Jacq et al, 1993;Hall et al, 1993Hall et al, , 1996Steen and Pedersen, 1993;Konwar, 1994;Sevenier et al, 1998). Fortunately, subsequent research had contributed to the improvement of the genetic transformation protocol in beets (Mannerlof et al, 1996;Joersbo et al, 1998;Kifle et al, 1999;Ingersoll et al, 1996;Ivic et al, 2001;Hisano et al, 2004), and the development of these genetic manipulation methodologies allowed many genes to be introduced into beets, especially in herbicide-resistance and disease-defense, resulted in great progresses in beet genetic breeding (D'Halluin et al, 1992;Mannerlof et al, 1996Mannerlof et al, , 1997Snyder et al, 1999;Dewar and May, 2000;Ivic et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…3A). All media used to isolate and culture B. vulgaris GCP contained w-propyl gallate, an inhibitor of lipoxygenase (EC 1.13.11.12; Krens et al, 1990Krens et al, , 1994Hall et al, 1993Hall et al, , 1994. It has been suggested that lipoxygenase plays a role in senescence (Bousquet and Thimann, 1980) and that the enzyme catalyzes synthesis of free radicals that oxidize ACC to ethylene by a nonenzymatic process (Kacperska and Kubacka-Zebalska, 1989).…”
Section: Electrophoresis Of Total Sds-extractable Proteinsmentioning
confidence: 99%
“…Papers that specify the method of alginate sterilization mostly report the use of autoclaving. The results vary from species to species: for example, protoplast division frequency of 4-22% in Nicotiana tabacum (Adaoha Mbanaso and Roscoe, 1982), 11-75% in Daucus carota (Grzebelus et al, 2012), 17-92% in Citrus sinensis (Niedz, 1993) and 20-30% in Beta vulgaris (Hall et al, 1993). In reports specifying filter sterilization of alginate, plating efficiency was 1-30% in Arabidopsis thaliana (Dovzhenko et al, 2003), 6-78% in Nicotiana tabacum (Dovzhenko et al, 1998) and 0-35% in Nicotiana sanderae (Draget et al, 1988).…”
Section: Discussionmentioning
confidence: 99%